Redistribution, Horizontal Inequity, and Reranking: Direct Taxation in the United Kingdom, 1977–2020 - Hérault, Nicolas; Jenkins, Stephen P. (Journal of Income Distribution®, 2024)
We decompose the redistributive effect of direct taxes into vertical, horizontal, and reranking components using the methods of Urban and Lambert (2008). In the first such application to the United Kingdom, and using yearly data covering 1977–2020, we find an increased redistributive effect over this period. There is, however, no clear trend in horizontal inequity, which forms a very small fraction of the total redistributive effect by comparison with reranking and, especially, vertical components. It is also the vertical component that best tracks trends in redistributive effect. We give specific attention to the choice of the bandwidth used to define ‘close equals’ in terms of pre-tax income. We also show that implausible estimates of the horizontal inequity component arise for some years, regardless of the bandwidth used.